2017
DOI: 10.1002/jcb.26143
|View full text |Cite
|
Sign up to set email alerts
|

β3‐Adrenergic Regulation of EPC Features Through Manipulation of the Bone Marrow MSC Niche

Abstract: Mesenchymal stem cells (MSCs) reside in a specific niche in the bone marrow, however, biological features of this niche are still not fully understood. Given the interactions of MSCs with endothelial cells in different tissues, bone marrow MSC niche may influence the biological features of endothelial progenitor cells (EPCs). To understand the role of the sympathetic nervous system in regulation of the MSC niche, we examined whether the manipulation of the MSC niche via β3-adrenergic signals will affect EPC fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…MSCs regulate the immuno-microenvironment by interacting with macrophages and regulating blood vessel formation by secreting angiogenic growth factors. This process involves interacting cells, including MSCs, macrophages, and vascular endothelial cells, as well as extracellular matrix molecules and cytokines, all of which constitute the MSC niche that is of great significance in regulating bone regeneration (Moore and Lemischka, 2006;Kuhn and Tuan, 2010;Vafaei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…MSCs regulate the immuno-microenvironment by interacting with macrophages and regulating blood vessel formation by secreting angiogenic growth factors. This process involves interacting cells, including MSCs, macrophages, and vascular endothelial cells, as well as extracellular matrix molecules and cytokines, all of which constitute the MSC niche that is of great significance in regulating bone regeneration (Moore and Lemischka, 2006;Kuhn and Tuan, 2010;Vafaei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1/IGF-2 bind to IGF-1R/IGF-2R on BMSCs and increase proliferation and self-renewal [83]. CXCL12 enhances BMSC colony forming capacity, which is promoted by activation of the b3-adrenergic neuron and followed by promotion of EPC colony forming potency [84].…”
Section: Bmsc/epc Nichementioning
confidence: 99%
“…Previous study showed that EPCs can be mobilized by SDF-1 cytokine and recruited to sites of neovascularization. 27,28 Furthermore, we found that increase in cEPCs was associated with increased circulating levels of VEGF, Ang1, and Ang2 cytokines that are considered as important activators of EPCs. 29,30 Previous studies showed that increases in angiogenic factors are associated with high proliferation and migration in EPCs.…”
Section: Discussionmentioning
confidence: 85%
“…Confirming this finding, we showed that SDF‐1 mRNA level increases in infants with ROP, which can induce EPC mobilization from the bone marrow to contribute into the growing network of blood vessels in the developing retina. Previous study showed that EPCs can be mobilized by SDF‐1 cytokine and recruited to sites of neovascularization …”
Section: Discussionmentioning
confidence: 99%